2020
DOI: 10.1093/cercor/bhaa348
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Foundations of Episodic Memory Remain Stable Throughout the Lifespan

Abstract: It has been suggested that specific forms of cognition in older age rely largely on late-life specific mechanisms. Here instead, we tested using task-fMRI (n = 540, age 6–82 years) whether the functional foundations of successful episodic memory encoding adhere to a principle of lifespan continuity, shaped by developmental, structural, and evolutionary influences. We clustered regions of the cerebral cortex according to the shape of the lifespan trajectory of memory activity in each region so that regions show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Approximate guessing rates for each individual was estimated by the number of incorrect answers to Q3, as the participants had indicated that they remembered the association in Q2, but then chose the wrong answer. These were subtracted from the number of correct answers before calculating the recollection index to correct for guessing (Sneve et al, 2015; Vidal-Piñeiro et al, 2021). The task presentation was controlled with E-Prime 2.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximate guessing rates for each individual was estimated by the number of incorrect answers to Q3, as the participants had indicated that they remembered the association in Q2, but then chose the wrong answer. These were subtracted from the number of correct answers before calculating the recollection index to correct for guessing (Sneve et al, 2015; Vidal-Piñeiro et al, 2021). The task presentation was controlled with E-Prime 2.0.…”
Section: Methodsmentioning
confidence: 99%
“…In case of 'No' answer to either Q1 or Q2 the trial ended without further questions. For memory analysis, a recollection index was calculated, correcting for guessing, by subtracting the number of incorrect answers to Q3 from the number of correct answers to Q3 6,55 . The recollection index, presented as the percentage of all trials, was 44% (sd = 19%).…”
Section: Study 1 Experimental Design and Proceduresmentioning
confidence: 99%
“…As we age, our cognitive abilities deteriorate, 1 without necessarily progressing to dementia. One of the earliest and most striking cognitive changes in the aging process is the alteration of memory.…”
Section: Narrativementioning
confidence: 99%